Theoretical Models of Buddhist Economy - Aktamov, Innokentii Galimalaevich; Badmatsyrenov, Timur Batorovich; Rodionov, Vladimir Alexandrovich; Nomogoeva, Victoria Vladimirovna; Badaraev, Damdin Dorzhievich (International Journal of Economics and Financial Issues, 2015)
The article is dedicated to the description of sociological approaches to studying the Buddhist economy. The researches of Buddhism have not sufficiently studied institutes of economy of Buddhist communities, and methods and mechanisms of the resource provision of their needs. The researches of Buddhism study mainly its religious and philosophical, political, cultic aspects, while economic ones are almost not touched upon. Along with this, Buddhism fulfilled important economic functions. Some Western researchers devoted their works to studying them. They laid basis for the development of scientific directions of the Buddhist economy. It is possible to single out several theories in the history of sociology. Problems related to the impact of Buddhism on economic development were researched within their framework. The article is an attempt to reveal basic variables of the theoretic analysis of economy in Buddhist communities and to describe the economic functions of Buddhist institutions. As a result of the analysis, three theoretical models of Buddhist economy that had non-equivalent impact on the science and in some periods competed were described. The article considers works of the Marxist direction and their interpretation of the Buddhist impact on economy. The contribution of M. Weber in the development of the Buddhist sociology is stated. The concept of the “Buddhist economy” of E. Schumacher is described. Keywords: Buddhism, Buddhist economy, K. Marx, M. Weber, E. Schumacher, Buryatia. JEL Classifications: H76; R11; R58; Z12